Spicing thing up: Synthetic cannabinoids - Spaderna, Max (2013)
RATIONALE: Recently, products containing synthetic cannabinoids, collectively referred to as Spice, are increasingly being used recreationally. OBJECTIVES: The availability, acute subjective effects—including self-reports posted on Erowid—laboratory detection, addictive potential, and regulatory challenges of the Spice phenomenon are reviewed. RESULTS: Spice is sold under the guise of potpourri or incense. Unlike THC, the synthetic cannabinoids present in Spice are high-potency, high-efficacy, cannabinoid-receptor full agonists. Since standard urine toxicology does not test for the synthetic cannabinoids in Spice, it is often used by those who want to avoid detection of drug use. These compounds have not yet been subjected to rigorous testing in humans. Acute psychoactive effects include changes in mood, anxiety, perception, thinking, memory, and attention. Adverse effects include anxiety, agitation, panic, dysphoria, psychosis, and bizarre behavior. Psychosis outcomes associated with Spice provide additional data linking cannabinoids and psychosis. Adverse events necessitating intervention by Poison Control Centers, law enforcement, emergency responders, and hospitals are increasing. Despite statutes prohibiting the manufacture, distribution, and sale of Spice products, manufacturers are replacing banned compounds with newer synthetic cannabinoids that are not banned. CONCLUSIONS: There is an urgent need for better research on the effects of synthetic cannabinoids to help clinicians manage adverse events and to better understand cannabinoid pharmacology in humans. The reported psychosis outcomes associated with synthetic cannabinoids contribute to the ongoing debate on the association between cannabinoids and psychosis. Finally, drug-detection tests for synthetic cannabinoids need to become clinically available.